2016
DOI: 10.1371/journal.pone.0167394
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Variation in Lifespans of Single Yeast Cells Is Related to Variation in Cell Size, Ribosomal Protein, and Division Time

Abstract: There is a large variability in lifespans of individuals even if they are genetically identical and raised under the same environmental conditions. Our recent system wide study of replicative aging in baker’s yeast predicts that protein biogenesis is a driver of aging. Here, we address how the natural variation in replicative lifespan within wild-type populations of yeast cells correlates to three biogenesis-related parameters, namely cell size, ribosomal protein Rpl13A-GFP levels, and division times. Imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 46 publications
7
70
1
Order By: Relevance
“…For example, potential candidates include genes in other heterochromatic regions, such as subtelomeric genes that encode metabolic enzymes or have mitochondrial functions (33), or Sir2-repressed genes with prolongevity functions (34), or critical processes influenced by rDNA transcription, such as ribosomal biogenesis, a potential regulator of yeast aging (35,36). Interestingly, a recent study (37) demonstrated that aggregation of a cell-cycle regulator, but not the previously reported loss of silencing at HM loci (38), causes sterility in old yeast cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, potential candidates include genes in other heterochromatic regions, such as subtelomeric genes that encode metabolic enzymes or have mitochondrial functions (33), or Sir2-repressed genes with prolongevity functions (34), or critical processes influenced by rDNA transcription, such as ribosomal biogenesis, a potential regulator of yeast aging (35,36). Interestingly, a recent study (37) demonstrated that aggregation of a cell-cycle regulator, but not the previously reported loss of silencing at HM loci (38), causes sterility in old yeast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as metabolic allometry can explain complex biological phenomena, such as population density, lifespan and evolution rate, on an organismal level 25 [31,37], it seems reasonable to assume that cellular allometry may have profound, although unexplored, biological consequences. One such example is the cellular phenotype seen in aging cells, where mitochondrial activity is reduced [38,39] and cell size increased, at least in specific cell types [39,40]. The age-dependent decline in mitochondrial activity could, in theory, be partly due to the underlying cell size increase.…”
Section: Metabolic Allometry and Size Homeostasis In Dividing Cellsmentioning
confidence: 99%
“…Cell volume increases in aging and the increase per division is predictive for the lifespan of cells 37 . Because macromolecular crowding is directly linked to cell volume, we aimed to determine how the volume of the cytosol changes in aging and assessed aged cells on the ultrastructural level.…”
Section: Volume Distribution Of Cellular Compartments In Yeast Replicmentioning
confidence: 99%
“…For example, it was suggested that oversized yeast cells have reduced molecular density 35 . One of the most dramatic features of yeast is a marked increase in cell size [36][37][38] . Concomitantly, yeast organelles like vacuoles 39 , the nucleus (including nucleoli 40,41 ), and mitochondria 42 can exhibit changes in morphology.…”
Section: Introductionmentioning
confidence: 99%